Al-Quran dan Pluralisme - Saihu Saihu (SUHUF, 2020)
This writing studies the Quranic arguments toward religious pluralism. In this writing, the author focuses the problem on how religious texts and literatures are responding religious plurality and individual attitude in the context of a multicultural society. It is based on the understanding of the collected and the opinions of many scholars, the writer argues that religious plurality is God’s design known as sunnatullah, which manifests in the life of mankind on the earth. Furthermore, the writer explains the idea of pluralism to have three important elements that could be the base in the interaction in a multi religion and cultures. The three elements are active engagement, constructive understanding, similarity in perception or in the term of Islam is known the moderate society (ummatan wasaṭan). If these three elements are actualized in society’s life, civil society will be created. It is an inclusive society, humanist, egalitarian, tolerant and democratic and is not limited by the differences and more than that this society can have full access to every public activity